Diagnosis and management of Alzheimer's disease. Issue 17 (9th September 2013) - Bansal, Sandeep; Walker, Rodney; Walker, Zuzana
Abstract: An accurate diagnosis of Alzheimer's disease warrants symptomatic treatment with an acetyl cholinesterase inhibitor or, in more severe disease, memantine. Here, the authors discuss the properties of the available treatment options.